AdS4/CFT3 from weak to strong string coupling - Binder,DJ; Chester,SM; Pufu,SS (Journal of High Energy Physics, 2020)
A bstract We consider the four-point function of operators in the stress tensor multiplet of the U( N ) k × U( N ) −k ABJM theory, in the limit where N is taken to infinity while N/k 5 is held fixed. In this limit, ABJM theory is holographically dual to type IIA string theory on AdS 4 × 3 at finite string coupling g s ∼ ( N/k 5 ) 1 / 4 . While at leading order in 1 /N , the stress tensor multiplet four-point function can be computed from type IIA supergravity, in this work we focus on the first subleading correction, which comes from tree level Witten diagrams with an R 4 interaction vertex. Using superconformal Ward identities, bulk locality, and the mass deformed sphere free energy previously computed to all orders in 1 /N from supersymmetric localization, we determine this R 4 correction as a function of N/k 5 . Taking its flat space limit, w